AKTIVITAS DIURETIK DAN SKRINING FITOKIMIA EKSTRAK ETANOL BIJI PEPAYA (Carica papaya L.) PADA TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus) (PHARMACON, 2014)
ABSTRACT Papaya (Carica papaya L.) is one of the most important fruit plant in the fulfillment of calcium and source of vitamins A and C. This research aimed to examine diuretics effecct in male rats and identification of chemical contents in the ethanol extract of papaya seed. As much 15 test animals were divided into 5 groups, that is negative control (0,5% CMC suspension), positive control (suspension furosemide 5,04 mg / kgBB), dose of extract 0,03 g/kgBB dose of extract 0,06 g/kgBB, and dose of extract 0,12 g/KgBB. The test is done by measuring of diuretics effect the urine volume incurred for 6 hours. Data obtained were analyzed with SPSS ver.20, one way ANOVA test and advanced test that is Duncan test. Statistical analysis showed a significant difference (Î±